HIT AND RUN: A Phenomenological Study of Manufacturer Experience in E-Commerce Transactions with the Pre-Order System from a Fiqh Muamalah Perspective - Asnita, Dessy; Mudrika, Syarifah (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
This research examines clothing manufacturers located in Bandung and Bekasi and a distributor in Medan to analyze the impact of the